2017
DOI: 10.1177/1747954117710507
|View full text |Cite
|
Sign up to set email alerts
|

Biological maturity and the anthropometric, physical and technical assessment of talent identified U16 Australian footballers

Abstract: 12This study compared biological maturation, anthropometric, physical and technical skill measures

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“… Straight dribbling, slalom dribbling + dual task Technical skills discriminate players from different performance levels Bennett et al [ 54 ] CS High Soccer AUS m 55 13.3 ± 1.2 OR comp. Attempted/completed dribbles, passes, touches, shots, and Total actions Technical skills discriminate players from different performance levels Cripps et al [ 55 ] CS Moderate Australian Football AUS ? 50 15.6 ± 0.4 OR exp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Straight dribbling, slalom dribbling + dual task Technical skills discriminate players from different performance levels Bennett et al [ 54 ] CS High Soccer AUS m 55 13.3 ± 1.2 OR comp. Attempted/completed dribbles, passes, touches, shots, and Total actions Technical skills discriminate players from different performance levels Cripps et al [ 55 ] CS Moderate Australian Football AUS ? 50 15.6 ± 0.4 OR exp.…”
Section: Resultsmentioning
confidence: 99%
“…Conducting an ‘outcome-related’ and ‘experimental’ methods approach in basketball, significantly better shooting (Cohen’s d = 1.11), passing ( d = 1.20), dribbling ( d = − 1.62) and defense ( d = − 1.05) skills were found for athletes selected to an elite regional team compared to non-selected athletes [ 66 ]. Also following an ‘outcome-related’ and ‘experimental’ methods approach, a study in Australian Football identified handball skills as being the most robust single measure (area under receiver operator curve = 76%, confidence interval = 62.5–89.5%) in a full logistic regression model to explain status (non-/state representation) [ 55 ]. In their study of young soccer players (U12–U15), Höner et al [ 46 ] investigated technical skills applying an ‘experimental’ method set-up and a combination of both ‘technique-related’ and ‘outcome-related’ method types.…”
Section: Resultsmentioning
confidence: 99%
“…These are likely inclusive of physical, technical and tactical capacities 3,23,24 , psychological constitution, and competition performance 25 . Multidisciplinary talent identification approaches have been shown to enhance the predictive outcomes of the athlete identification at junior levels of the Australian football talent pathway process 23,24 . However, research is yet to explore the multitude of factors longitudinally to establish if particular qualities are more or less stable within junior athletes or important for career outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Again, comparable to observations in senior soccer players, anthropometric and morphologic differences are also suggested to be present when comparing playing standards of youth soccer players. Cripps et al (2017) found that talent identified individual's possessed greater standing stature and an advanced maturity status than non-talent identified groups of U16…”
Section: Anthropometric and Morphologic Characteristics Of Youth Soccermentioning
confidence: 95%